Clinical presentations and dispositions of transient ischemic attack and minor stroke patients at the emergency department of a tertiary hospital in southern Thailand: A retrospective study - Tanawin Sakarin; Tippawan Liabsuetrakul (Hong Kong Journal of Emergency Medicine)
Abstract Objective To assess the dispositions, management, and clinical outcomes of TIAMS patients in ED to improve the quality of management in ED. Material and Method A descriptive retrospective study was conducted in ED patients aged >18 years diagnosed with TIAMS in the ED from 1 January 2018, to 31 January 2019. Data regarding terms of clinical presentation, examination, management, disposition, and adverse events were collected. Results Three hundred and sixty‐three TIAMS patients were enrolled in the study. Majority of the patients aged <45 years were admitted or referred (15.4%). The highest proportion of patients whose onset times from the last normal were less than 4.5 h were admitted to the EDOU (55.6%), while all patients whose onset times from the last normal were more than 48 h were discharged. Patients with abnormal cerebellar signs or atrial fibrillation were less likely to be discharged from the hospital. Patients with lower National Institutes of Health Stroke Scale (NIHSS) and ABCD2 scores tended to be discharged. Conclusion Among TIAMS patients, age, symptom onset, presence of atrial fibrillation, positive cerebellar signs, and severity scores influenced the disposition. There was no difference in adverse events among disposition groups.